2013
DOI: 10.1093/ckj/sft107
|View full text |Cite
|
Sign up to set email alerts
|

The variable course of women with X-linked Alport Syndrome

Abstract: X-linked Alport syndrome (XLAS) arises from mutations in the COL4A5 gene encoding the α5-chain of type IV collagen and is associated with hematuria, ocular abnormalities and high-tone sensorineural hearing loss. Nearly all affected males have decreased kidney function resulting in end-stage renal disease (ESRD) as early as the second decade of life. It was long thought that affected females had a benign outcome; however, in recent decades, it has become quite clear that they too are at risk for developing neph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
4
1
1
Order By: Relevance
“…Nephrotic syndrome is rarely described. Raju et al [9] reported 2 young females with the X-linked form with hematuria, nephrotic-range proteinuria, and renal insufficiency In our patient, the sudden onset of nephrotic syndrome is not consistent with the pattern of progressing proteinuria observed in AS. Her clinical features, however, are in accordance with the histologic diagnosis of MN.…”
Section: Discussioncontrasting
confidence: 73%
“…Nephrotic syndrome is rarely described. Raju et al [9] reported 2 young females with the X-linked form with hematuria, nephrotic-range proteinuria, and renal insufficiency In our patient, the sudden onset of nephrotic syndrome is not consistent with the pattern of progressing proteinuria observed in AS. Her clinical features, however, are in accordance with the histologic diagnosis of MN.…”
Section: Discussioncontrasting
confidence: 73%
“…La prevalencia del SA es 1 en 50.000 nacidos vivos [6]. El curso clínico es muy variable, puede presentar hematuria micro y macroscópica, proteinuria, hipertensión, sordera y algunos pueden progresar a enfermedad renal crónica terminal [7]. Además se han descrito múltiples manifestaciones oculares las cuales pueden ser asintomáticas [8] como las cataratas que presenta este paciente.…”
Section: Discussionunclassified
“…Diseases resulting from chronic endothelial injury, that is, chronic thrombotic microangiopathy or transplant glomerulopathy, show primarily an expansion of the lamina rara interna, but no abnormalities along the lamina densa perse (shown in Fig. [16][17][18]. Immune complex-mediated glomerulonephritides with signs of resolution present with foci of electron lucency within the capillary walls and structural irregularities that can mimic HN (shown in Fig.…”
Section: Electron Microscopymentioning
confidence: 99%
“…Heterozygote females with X-linked Alport show a mosaic discontinuous pattern of GBM staining for alpha 5 type collagen IV due to the Lyon effect, with normal or mutated alleles activated in the individual cells (shown in Fig. 6 ) [ 2 , 8 , 18 ].…”
Section: Immunofluorescence Microscopymentioning
confidence: 99%